POLITICAL MODERNIZATION AS A FORM OF POLITICAL DEVELOPMENT (Intent Research Scientific Journal, 2023)
The term "modernization" does not refer to the entire period of social progress, but only to one of its stages - the modern one. Translated into English, "modernization" means "modernization". Modernization theory is designed to explain how countries that are "late" in their development can achieve the economic and social successes that the leading countries of the world have. Modernization indicates the way of entering the world community, which is understood as the world economic system of capitalism. The desire of scientists to identify the sources, nature and direction of political changes in societies that change models of economic and political development has led to the formation of the theory of political modernization. The political improvement of public life, the democratization of government and control bodies are naturally based on political modernization. Political modernization creates conditions for the emergence of new, political institutions. Existing political institutions will also develop and acquire a new essence. Therefore, various reforms, renovations and modernization processes are of great importance in the political life of Uzbekistan.